2003
DOI: 10.2306/scienceasia1513-1874.2003.29.365
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An enhanced biological phosphorus removal (EBPR) process is currently one of the most economical and practical ways to reduce high phosphorus content in wastewaters. Under sequential conditions of anaerobic and aerobic environments, the phosphateaccumulating organisms (PAOs), which are able to accumulate intracellular phosphorus in a much higher quantity than other microorganisms, become predominant. In anaerobic stage, the PAOs absorb readily biodegradable substrate by destroying their storage polyphosphate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, the P/C ratios in both reactors were higher than models (0.50 and 0.42 P-mol/C-mol) developed under lower temperature (Oehmen et al 2005e, Smolders et al 1994. Panswad et al (2003) also observed that the specific phosphorus release rates increased with the increase of temperature. The higher P/C ratios should be partly due to higher maintenance energy required for PAO at high temperature.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the P/C ratios in both reactors were higher than models (0.50 and 0.42 P-mol/C-mol) developed under lower temperature (Oehmen et al 2005e, Smolders et al 1994. Panswad et al (2003) also observed that the specific phosphorus release rates increased with the increase of temperature. The higher P/C ratios should be partly due to higher maintenance energy required for PAO at high temperature.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…Previous research demonstrated that the employment of EBPR in tropical climate was challenging due to the proliferation of GAOs when the temperature was higher (25 o C~30 °C) (Lopez-Vazquez et al 2009a, Lopez-Vazquez et al 2009b, Panswad et al 2003, Whang and Park 2006. However, a few successful EBPR processes operated at high temperature have shone some light on the feasibility of high temperature EBPR (Freitas et al 2009, Ong et al 2013, Winkler et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Studies had contradictory results regarding EBPR efficiency and stability at different temperature ranges, but it was widely agreed that low temperature (below 20°C) favored PAO against GAO in many lab-scale studies (Whang and Park, 2002, Panswad et al, 2003, Whang and Park, 2006. Nevertheless, the reason for cold temperature favoring PAO was still under debate (Gebremariam et al, 2011).…”
Section: Enhanced Biological Phosphorous Removal (Ebpr)mentioning
confidence: 99%